DIVERSITY OF BATS (CHIROPTERA) IN VARIOUS HABITATS IN BUALEMO SUB-DISTRICT, CENTRAL SULAWESI, INDONESIA - Ummu Muthi'ah Ramadhana; Riska Khairiah; Masrianih; Yulia Windarsih; Riski Aprianto; Alpon Katili; Ansar Sayende; Lili Shafdila Nursin; Ellena Yusti (BRIN Publishing (Penerbit BRIN), 2025)
Bats play an important role in ecosystems as pollinators, seed dispersers, and insect pestcontrollers. Indonesia has the highest bat diversity in Southeast Asia, with Sulawesi as a globalendemicity hotspot. However, data from Central Sulawesi remain limited, particularly amid threats ofhabitat degradation and hunting toward bats. This study aims to assess the diversity and habitatpreferences of Yangochiroptera and Yinpterochiroptera in Bualemo sub-district, Central Sulawesi. Datawere collected for 31 nights in June and July 2024 using mist nets and harp traps across plantationsnear cave, plantations, secondary forests, and rivers. A total of 474 individuals from 5 families and 23species were identified. Yangochiroptera consisted of 113 individuals from 4 families and 13 species.Meanwhile, Yinpterochiroptera consisted of 361 individuals from one family and 10 species, withCynopterus luzoniensis and Rousettus amplexicaudatus as the most frequently found species. TheShannon-Wiener diversity index (H' = 1.534-2.210), indicating moderate diversity, while the evennessindex (E = 0.489-0.705), suggesting more balanced distribution in vegetated habitats.Yinpterochiroptera were mainly found in plantations rich in food sources, such as Ficus trees, whileDobsonia exoleta and Harpyionycteris celebensis were restricted to secondary forests. Yangochiropteradisplayed distinct habitat preferences. Rhinolophus sp.a dominated plantations near cave, whereasRhinolophus sp.b occurred only in secondary forests. These preferences were influenced by foodavailability, vegetation structure, and environmental conditions such as rainfall and moon phase. Thesefindings emphasize the importance of conserving various habitat types to maintain the diversity andstability of bat populations, while raising public awareness of their ecological role.